Heat-resistant and aging-resistant modified silicone rubber material
By adding specific ratios of octahydrogen-based cage silsesquioxane, nano-scale tin oxide and iron trioxide to the silicone rubber material, the problem of insufficient heat resistance and aging performance of traditional silicone rubber materials at high temperatures is solved, and the high temperature stability and aging resistance of the material are improved.
Patent Information
- Application Number
- CN202510152997.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-12
- Publication Date
- 2025-04-22
AI Technical Summary
Traditional silicone rubber materials show insufficient heat resistance and aging performance in high temperature and long-term service environments, making it difficult to meet the performance requirements of electrical products, seals and components in high temperature environments.
Vinyl silicone rubber is used as the main material, and octahydrogen-based cage-type silsesquioxane, nano-scale tin oxide, iron trioxide and other components are added. Through specific ratios and process treatment, a silicone rubber composite material with excellent heat resistance and anti-aging properties is formed.
It significantly improves the heat resistance temperature and aging stability of silicone rubber materials, enhances its thermal stability and physical properties, such as hardness and tensile strength, ensuring that the material maintains good mechanical and electrical properties at high temperatures.
Smart Images

Figure CN119859413A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicone rubber materials, in particular to a heat-resistant and aging-resistant modified silicone rubber material. Background Art
[0002] With the development of industrial technology and the improvement of product performance requirements, although traditional silicone rubber materials have good elasticity, wear resistance and insulation properties, their heat resistance and aging performance are obviously insufficient under high temperature and long-term service environments; especially electrical products, seals and components working in high temperature environments require silicone rubber materials with higher heat resistance and aging resistance; therefore, modified silicone rubber materials with excellent heat resistance, aging resistance and stable performance are developed;
[0003] The existing technical methods have certain limitations in practical applications: the added fillers are not completely evenly distributed, which can easily cause uneven distribution of internal material properties; on the other hand, adding excessive fillers and modifiers will significantly increase the cost of the material and may limit the processing performance and flexibility of silicone rubber. Summary of the invention
[0004] The object of the present invention is to provide a heat-resistant and aging-resistant modified silicone rubber material to solve the problems raised in the above background technology.
[0005] To achieve the above object, the present invention provides the following technical solution: a heat-resistant and aging-resistant modified silicone rubber material, characterized in that its raw materials include, by weight:
[0006] 100 parts of vinyl silicone rubber, 3-12 parts of octahydrogen cage silsesquioxane, 6-18 parts of modified white carbon black, 3-12 parts of nano-sized tin oxide, 3-5 parts of ferric oxide, 1-10 parts of ethyl orthosilicate, 0.5-5 parts of dibutyltin dilaurate, and 1-3.8 parts of 2,6-di-tert-butyl-4-methylphenol;
[0007] Under the action of an electric stirrer, the crosslinking agent octahydrogen cage silsesquioxane, the reinforcing filler modified white carbon black, the heat-resistant filler nano-sized tin oxide, the heat-resistant additive ferric oxide, the vulcanizing agent ethyl orthosilicate, and the catalyst dibutyl tin dilaurate are added to the vinyl silicone rubber in sequence, and after being fully stirred, the mixture is placed in a vacuum oven at room temperature to remove bubbles, the vacuum degree is controlled at -0.1 MPa, and the mixture is cured at room temperature to obtain a silicone rubber composite material.
[0008] Preferably, the vinyl silicone rubber is polysiloxane containing vinyl end groups with a functionality of 2 or more and a degree of polymerization of 1000 or more.
[0009] Preferably, the octahydrogen cage silsesquioxane is prepared according to the following process: ferric chloride and concentrated hydrochloric acid are added to a container, and then methanol, toluene and n-hexane are added to the container, and trichlorosilane is dissolved in n-hexane after stirring evenly, and slowly added dropwise to the container within 3 hours. After the dropwise addition is completed, the stirring is continued for 2 hours, and the reaction process is carried out at 30° C. and the reaction is carried out under the protection of N2 gas to separate the n-hexane layer, and anhydrous CaCL2 and anhydrous K2CO3 are added to the reaction solution, and the stirred and filtered, and the filtered liquid is distilled under reduced pressure, concentrated to crystal precipitation, and the obtained product is collected, and then washed with n-hexane, and dried at 70° C. for 5 hours to obtain the product octahydrogen cage silsesquioxane, and the dried product octahydrogen cage silsesquioxane is purified to remove impurities and by-products therein;
[0010] Finally, pure octahydrogen cage silsesquioxane was obtained by recrystallization.
[0011] Preferably, in the process of preparing octahydrogen cage silsesquioxane, the weight ratio of ferric chloride, concentrated hydrochloric acid, methanol, toluene, trichlorosilane and n-hexane is 15-50:5-30:10-40:10-55:5-15:120-280.
[0012] Preferably, the modified silica is prepared according to the following process: adding silica and ionic liquid modifier in a certain proportion into an electric stirrer;
[0013] The raw materials are fully stirred and mixed under the action of an electric stirrer so that the ionic liquid modifier is evenly coated on the surface of the silica. During the stirring process, an acetone solvent is added to promote the dissolution and dispersion of the ionic liquid. Then, the mixture is placed in a constant temperature water bath at 30° C. for reaction so that the ionic liquid modifier interacts with the functional groups on the surface of the silica.
[0014] After the reaction is completed, the mixture is dried at a temperature of 150° C. for 3 hours to remove unreacted ionic liquid and solvent.
[0015] The dried modified silica is sieved to remove impurities and uneven particles to obtain modified silica.
[0016] Preferably, the ratio of the ionic liquid, white carbon black and acetone solvent is 10-50:500:1-5.
[0017] Preferably, the ionic liquid is a dialkyl imidazole halide, the cation is a C4 or C6 alkyl substituent, the anion is Cl-, and the ionic liquid preparation process is as follows:
[0018] Raw material preparation: alkyl imidazole and halogenated hydrocarbon are selected as raw materials, and sodium chloride is used as anion source;
[0019] Synthesis reaction: Under the conditions of 85°C and 500 rpm stirring speed, alkyl imidazole and halogenated hydrocarbon are reacted for 3-5 hours to generate dialkyl imidazole halide intermediate;
[0020] Then, the generated dialkyl imidazolium halide intermediate is subjected to anion exchange reaction with sodium chloride to generate the desired dialkyl imidazolium chloride ionic liquid.
[0021] Post-treatment: washing, drying and purification are performed on the generated dialkyl imidazolium chloride ionic liquid to remove unreacted raw materials and impurities to obtain a pure ionic liquid.
[0022] Compared with the prior art, the invention has the following beneficial effects: the heat-resistant and aging-resistant modified silicone rubber material of the invention is mainly made of vinyl silicone rubber, and is simultaneously added with octahydrogen cage silsesquioxane, nano-sized tin oxide, and ferric oxide to cooperate with the material, and the ratio of the three is adjusted so that the three can play the best synergistic role. The chemical structure of octahydrogen cage silsesquioxane is (RSiO1.5)8, wherein R represents a hydrogen atom (H) to form an octahedral silsesquioxane. The Si-O bonds in the octahedral structure form a stable cage skeleton, and the Si atoms at the eight vertices are connected to hydrogen atoms, such as Si-H bonds. In the cage structure, Si atoms and O atoms form covalent bonds by sharing electron pairs, thereby constructing a three-dimensional cage structure composed of Si-O-Si with a cavity. The cage structure enables the octahydrogen cage silsesquioxane to have unique physical and chemical properties, such as high thermal stability and good dielectric properties. and optical properties, and the top corners are connected with Si-H bonds, which have high reactivity. The Si-H in the octahydrogen cage silsesquioxane reacts with the Si-Vi in the vinyl silicone rubber to introduce the cage silsesquioxane into the vinyl silicone rubber to form a cross-linked network structure, which improves the heat resistance of the silicone rubber material. The nano-scale tin oxide inhibits the oxidation process of the silicone rubber side chain, thereby improving the heat resistance of the silicone rubber. Ferric oxide can prevent the oxidation reaction of silicone rubber at high temperatures, thereby delaying the aging process of silicone rubber. Ferric oxide has high thermal stability and can maintain a stable chemical structure at high temperatures, thereby enhancing the thermal stability of silicone rubber. The addition of ferric oxide can also improve the physical properties of silicone rubber, such as improving hardness and tensile strength, thereby further improving the high temperature resistance of silicone rubber, so that the silicone rubber maintains a high mechanical strength while giving the material excellent heat resistance and aging resistance.
[0023] In the preparation process of optimized modified silica, silica and ionic liquid are used as raw materials, and acetone solvent is added to promote the dissolution and dispersion of ionic liquid, so that the ionic liquid modifier interacts with the functional groups on the surface of silica. The ionic liquid carries polar groups such as long-chain hydroxyl and carboxyl groups, which have strong surface activity and can form a stable adsorption layer on the surface of silica, change the surface structure of silica, reduce the electrostatic repulsion between silica particles, make silica easier to be broken up during the dispersion process, form a more uniform dispersion system, solve the problem of uneven distribution of internal performance of the material caused by uneven distribution of fillers, and reduce the cost of materials by controlling the addition amount of silica and ionic liquid modifier, and the modified silica has better compatibility with vinyl silicone rubber, which improves the processing performance and use flexibility of silicone rubber;
[0024] Modified white carbon black is obtained and added into the system. It is evenly dispersed in the system and has a synergistic effect with the octahydrogen cage silsesquioxane, heat stabilizer and heat-resistant additive in the system. The hydroxyl groups on the surface of white carbon black are combined with the polysiloxane molecules in the vinyl silicone rubber through hydrogen bonds to form a three-dimensional network structure, which effectively restricts the movement of the polysiloxane molecular chain, thereby playing a reinforcing effect, improving the strength and heat resistance of the silicone rubber, and further improving the conductivity, wear resistance and thermal stability of the material.
[0025] At the same time, 2,6-di-tert-butyl-4-methylphenol is added to capture the free radicals generated during the thermal oxidation aging of silicone rubber, significantly reduce the generation of oxidation products, improve the thermal stability of the rubber material, give the material excellent heat resistance, slow down the aging of the rubber material, and give the rubber material excellent aging resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a flow chart for preparing octahydrogen cage-type silsesquioxane of the present invention;
[0027] Figure 2 The present invention is a flow chart for preparing modified silica; Figure 3 The figure is a flow chart of the preparation of the ionic liquid of the present invention. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] See also Figure 1-2 , a technical solution provided by the present invention:
[0030] Embodiment 1:
[0031] The invention provides a heat-resistant and aging-resistant modified silicone rubber material, wherein the raw materials include, by weight: 100 parts of vinyl silicone rubber, 5 parts of octahydrogen cage-type silsesquioxane, 10 parts of modified white carbon black, 5 parts of nano-grade tin oxide, 3 parts of ferric oxide, 4 parts of tetraethyl orthosilicate, 2.5 parts of dibutyltin dilaurate, and 3 parts of 2,6-di-tert-butyl-4-methylphenol;
[0032] Under the action of an electric stirrer, crosslinking agent octahydrogen cage silsesquioxane, reinforcing filler modified white carbon black, heat-resistant filler nano-sized tin oxide, heat-resistant additive ferric oxide, vulcanizing agent ethyl orthosilicate, and catalyst dibutyltin dilaurate are sequentially added to vinyl silicone rubber, fully stirred, put into a vacuum oven at room temperature to remove bubbles, the vacuum degree is controlled at -0.1 MPa, and cured at room temperature to obtain a silicone rubber composite material;
[0033] Wherein, the vinyl silicone rubber adopts polysiloxane containing vinyl end groups with a functionality of 2 or more and a degree of polymerization of 1000 or more;
[0034] Octahydrogen cage silsesquioxane is prepared according to the following process: ferric chloride and concentrated hydrochloric acid are added to a container, and then methanol, toluene and n-hexane are added to the container, and trichlorosilane is dissolved in n-hexane after stirring evenly, and slowly added to the container within 3 hours. After the addition is completed, continue to stir rapidly for 2 hours. The reaction process of octahydrogen cage silsesquioxane is carried out at 30° C. and under the protection of N2 gas; then, the n-hexane layer is separated, anhydrous CaCL2 and anhydrous K2CO3 are added to the reaction solution, stirred and filtered, and the filtered liquid is distilled under reduced pressure and concentrated until crystals are precipitated, the obtained product is collected, and then washed with n-hexane, and dried at 70° C. for 5 hours to obtain the product octahydrogen cage silsesquioxane, and the dried product octahydrogen cage silsesquioxane is purified to remove impurities and by-products therein; finally, pure octahydrogen cage silsesquioxane is obtained by recrystallization;
[0035] In the process of preparing octahydrogen cage silsesquioxane, the weight ratio of ferric chloride, concentrated hydrochloric acid, methanol, toluene, trichlorosilane and n-hexane is 15:25:30:35:7:180;
[0036] The modified silica is prepared according to the following process: placing silica and ionic liquid modifier in an electric stirrer at a ratio of 15:500; fully stirring and mixing the raw materials under the action of the electric stirrer so that the ionic liquid modifier is evenly coated on the surface of the silica; during the stirring process, adding acetone solvent to promote the dissolution and dispersion of the ionic liquid; then, placing the mixture in a 30°C constant temperature water bath for reaction so that the ionic liquid modifier interacts with the functional groups on the surface of the silica; after the reaction is completed, drying the mixture, the drying temperature is controlled at 150°C, and the drying time is 3 hours to remove unreacted ionic liquid and solvent; the dried modified silica is sieved to remove impurities and uneven particles, and the modified silica is obtained after sieving;
[0037] The ionic liquid adopts dialkyl imidazole halide, the cation is a C4, C6 alkyl substituent, the anion is Cl-, and the preparation process of the ionic liquid is as follows:
[0038] Raw material preparation: alkyl imidazole and halogenated hydrocarbon are selected as raw materials, and sodium chloride is used as anion source;
[0039] Synthesis reaction: Under the conditions of 85°C and 500 rpm stirring speed, alkyl imidazole and halogenated hydrocarbon are reacted for 3-5 hours to generate dialkyl imidazole halide intermediate;
[0040] Then, the generated dialkyl imidazolium halide intermediate is subjected to anion exchange reaction with sodium chloride to generate the desired dialkyl imidazolium chloride ionic liquid;
[0041] Post-treatment: washing, drying and purification are performed on the generated dialkyl imidazolium chloride ionic liquid to remove unreacted raw materials and impurities to obtain a pure ionic liquid.
[0042] Embodiment 2:
[0043] The invention provides a heat-resistant and aging-resistant modified silicone rubber material, wherein the raw materials include, by weight: 100 parts of vinyl silicone rubber, 8 parts of octahydrogen cage-type silsesquioxane, 15 parts of modified white carbon black, 8 parts of nano-grade tin oxide, 4 parts of ferric oxide, 5 parts of ethyl orthosilicate, 3 parts of dibutyltin dilaurate, and 2 parts of 2,6-di-tert-butyl-4-methylphenol;
[0044] Under the action of an electric stirrer, crosslinking agent octahydrogen cage silsesquioxane, reinforcing filler modified white carbon black, heat-resistant filler nano-sized tin oxide, heat-resistant additive ferric oxide, vulcanizing agent ethyl orthosilicate, and catalyst dibutyltin dilaurate are sequentially added to vinyl silicone rubber, fully stirred, put into a vacuum oven at room temperature to remove bubbles, the vacuum degree is controlled at -0.1 MPa, and cured at room temperature to obtain a silicone rubber composite material;
[0045] Wherein, the vinyl silicone rubber adopts polysiloxane containing vinyl end groups with a functionality of 2 or more and a degree of polymerization of 1000 or more;
[0046] Octahydrogen cage silsesquioxane is prepared according to the following process: ferric chloride and concentrated hydrochloric acid are added to a container, and then methanol, toluene and n-hexane are added to the container, and trichlorosilane is dissolved in n-hexane after stirring evenly, and slowly added to the container within 3 hours. After the addition is completed, continue to stir rapidly for 2 hours. The reaction process of octahydrogen cage silsesquioxane is carried out at 30° C. and under the protection of N2 gas; then, the n-hexane layer is separated, anhydrous CaCL2 and anhydrous K2CO3 are added to the reaction solution, stirred and filtered, and the filtered liquid is distilled under reduced pressure and concentrated until crystals are precipitated, the obtained product is collected, and then washed with n-hexane, and dried at 70° C. for 5 hours to obtain the product octahydrogen cage silsesquioxane, and the dried product octahydrogen cage silsesquioxane is purified to remove impurities and by-products therein; finally, pure octahydrogen cage silsesquioxane is obtained by recrystallization;
[0047] In the process of preparing octahydrogen cage silsesquioxane, the weight ratio of ferric chloride, part concentrated hydrochloric acid, part methanol, part toluene, part trichlorosilane, and n-hexane is 25:10:20:25:10:150;
[0048] The modified silica is prepared according to the following process: placing silica and ionic liquid modifier in an electric stirrer at a ratio of 15:500; fully stirring and mixing the raw materials under the action of the electric stirrer so that the ionic liquid modifier is evenly coated on the surface of the silica; during the stirring process, adding acetone solvent to promote the dissolution and dispersion of the ionic liquid; then, placing the mixture in a 30°C constant temperature water bath for reaction so that the ionic liquid modifier interacts with the functional groups on the surface of the silica; after the reaction is completed, drying the mixture, the drying temperature is controlled at 150°C, and the drying time is 3 hours to remove unreacted ionic liquid and solvent; the dried modified silica is sieved to remove impurities and uneven particles, and the modified silica is obtained after sieving;
[0049] The ionic liquid adopts dialkyl imidazole halide, the cation is a C4, C6 alkyl substituent, the anion is Cl-, and the preparation process of the ionic liquid is as follows:
[0050] Raw material preparation: alkyl imidazole and halogenated hydrocarbon are selected as raw materials, and sodium chloride is used as anion source;
[0051] Synthesis reaction: Under the conditions of 85°C and 500 rpm stirring speed, alkyl imidazole and halogenated hydrocarbon are reacted for 3-5 hours to generate dialkyl imidazole halide intermediate;
[0052] Then, the generated dialkyl imidazolium halide intermediate is subjected to anion exchange reaction with sodium chloride to generate the desired dialkyl imidazolium chloride ionic liquid;
[0053] Post-treatment: washing, drying and purification are performed on the generated dialkyl imidazolium chloride ionic liquid to remove unreacted raw materials and impurities to obtain a pure ionic liquid.
[0054] Embodiment 3:
[0055] The invention provides a heat-resistant and aging-resistant modified silicone rubber material, wherein the raw materials include, by weight: 100 parts of vinyl silicone rubber, 8 parts of octahydrogen cage-type silsesquioxane, 15 parts of modified white carbon black, 3-12 parts of nano-grade tin oxide, 5 parts of ferric oxide, 8 parts of tetraethyl orthosilicate, 4 parts of dibutyltin dilaurate, and 1.5 parts of 2,6-di-tert-butyl-4-methylphenol;
[0056] Under the action of an electric stirrer, crosslinking agent octahydrogen cage silsesquioxane, reinforcing filler modified white carbon black, heat-resistant filler nano-sized tin oxide, heat-resistant additive ferric oxide, vulcanizing agent ethyl orthosilicate, and catalyst dibutyltin dilaurate are sequentially added to vinyl silicone rubber, fully stirred, put into a vacuum oven at room temperature to remove bubbles, the vacuum degree is controlled at -0.1 MPa, and cured at room temperature to obtain a silicone rubber composite material;
[0057] Wherein, the vinyl silicone rubber adopts polysiloxane containing vinyl end groups with a functionality of 2 or more and a degree of polymerization of 1000 or more;
[0058] Octahydrogen cage silsesquioxane is prepared according to the following process: ferric chloride and concentrated hydrochloric acid are added to a container, and then methanol, toluene and n-hexane are added to the container, and trichlorosilane is dissolved in n-hexane after stirring evenly, and slowly added to the container within 3 hours. After the addition is completed, continue to stir rapidly for 2 hours. The reaction process of octahydrogen cage silsesquioxane is carried out at 30° C. and under the protection of N2 gas; then, the n-hexane layer is separated, anhydrous CaCL2 and anhydrous K2CO3 are added to the reaction solution, stirred and filtered, and the filtered liquid is distilled under reduced pressure and concentrated until crystals are precipitated, the obtained product is collected, and then washed with n-hexane, and dried at 70° C. for 5 hours to obtain the product octahydrogen cage silsesquioxane, and the dried product octahydrogen cage silsesquioxane is purified to remove impurities and by-products therein; finally, pure octahydrogen cage silsesquioxane is obtained by recrystallization;
[0059] In the process of preparing octahydrogen cage silsesquioxane, the weight ratio of ferric chloride, concentrated hydrochloric acid, methanol, toluene, trichlorosilane and n-hexane is 35:20:15:30:12:200;
[0060] The modified silica is prepared according to the following process: placing silica and ionic liquid modifier in an electric stirrer at a ratio of 15:500; fully stirring and mixing the raw materials under the action of the electric stirrer so that the ionic liquid modifier is evenly coated on the surface of the silica; during the stirring process, adding acetone solvent to promote the dissolution and dispersion of the ionic liquid; then, placing the mixture in a 30°C constant temperature water bath for reaction so that the ionic liquid modifier interacts with the functional groups on the surface of the silica; after the reaction is completed, drying the mixture, the drying temperature is controlled at 150°C, and the drying time is 3 hours to remove unreacted ionic liquid and solvent; the dried modified silica is sieved to remove impurities and uneven particles, and the modified silica is obtained after sieving;
[0061] The ionic liquid adopts dialkyl imidazole halide, the cation is a C4, C6 alkyl substituent, the anion is Cl-, and the preparation process of the ionic liquid is as follows:
[0062] Raw material preparation: alkyl imidazole and halogenated hydrocarbon are selected as raw materials, and sodium chloride is used as anion source;
[0063] Synthesis reaction: Under the conditions of 85°C and 500 rpm stirring speed, alkyl imidazole and halogenated hydrocarbon are reacted for 3-5 hours to generate dialkyl imidazole halide intermediate;
[0064] Then, the generated dialkyl imidazolium halide intermediate is subjected to anion exchange reaction with sodium chloride to generate the desired dialkyl imidazolium chloride ionic liquid.
[0065] Post-treatment: washing, drying and purification are performed on the generated dialkyl imidazolium chloride ionic liquid to remove unreacted raw materials and impurities to obtain a pure ionic liquid.
[0066] The properties of each embodiment are compared in the following table:
[0067]
[0068] Based on the above, when using the formula provided by the present invention, when 8 parts of octahydrogen cage silsesquioxane are added, the molar ratio of Si—H in the octahydrogen cage silsesquioxane to Si—Vi in the vinyl silicone rubber is 4:1, and the thermal stability of the silicone rubber reaches the best, because the octahydrogen cage silsesquioxane is a three-dimensional cage-like inorganic skeleton composed of Si—O—Si, and this structure gives the material good thermal stability, and each molecule has 8 active points that can participate in crosslinking, that is, the Si—H bonds at the vertices of the octahydrogen cage silsesquioxane react with the Si—Vi in the silicone rubber to form a three-dimensional network structure, which reduces the flexibility of the chain segments and thereby increases the decomposition temperature of the silicone rubber. As the molar ratio continues to increase, the decomposition temperature decreases instead. This is because when the content of silicon-hydrogen bonds is too high, the active points are idle, the crosslinking points are dispersed, and the crosslinking density decreases instead. In addition, the Si—H bonds in the excess octahydrogen cage silsesquioxane will decompose first, resulting in thermal weight loss and a decrease in the decomposition temperature.
[0069] When 15 parts of white carbon black is added, the tensile strength of silicone rubber reaches the best. As the amount of white carbon black continues to increase, the tensile strength and shear strength decrease. This is because excessive white carbon black silicone rubber is difficult to disperse in the base rubber, resulting in agglomeration, which in turn affects the mechanical properties of silicone rubber.
[0070] When 8 parts of tin oxide are added, the heat resistance of the silicone rubber is the best, because tin oxide inhibits the oxidation process of the silicone rubber side chain, thereby improving the heat resistance of the silicone rubber. However, as the amount of tin oxide increases, the heat resistance of the silicone rubber decreases. This may be because SnO2 itself has a certain oxidizing property. When the amount added is too much, its oxidizing effect on the silicone rubber is greater than preventing the oxidation of the silicone rubber side chain through valence change.
[0071] Therefore, the best raw materials are 100 parts by weight of vinyl silicone rubber, 8 parts of octahydrogen cage silsesquioxane, 15 parts of modified white carbon black, 8 parts of nano-sized tin oxide, 4 parts of ferric oxide, 5 parts of tetraethyl orthosilicate, 3 parts of dibutyl tin dilaurate, and 2 parts of 2,6-di-tert-butyl-4-methylphenol.
[0072] Octahydrogen cage silsesquioxane is added to improve the interfacial bonding between vinyl silicone rubber and modified silica; 2,6-di-tert-butyl-4-methylphenol is added to capture free radicals and delay the aging process of silicone rubber; nano-scale tin oxide inhibits the oxidation process of silicone rubber side chains, thereby improving the heat resistance of silicone rubber; the addition of ferric oxide can prevent the oxidation reaction of silicone rubber at high temperature, thereby delaying the aging process of silicone rubber, and ferric oxide has high thermal stability and can maintain a stable chemical structure at high temperature, thereby enhancing the thermal stability of silicone rubber. The addition of ferric oxide can also improve the physical properties of silicone rubber, such as improving hardness and tensile strength, so that silicone rubber maintains high mechanical strength while giving the material excellent heat resistance and aging resistance; the addition of ethyl orthosilicate and dibutyltin dilaurate changes the vulcanization speed of vinyl silicone rubber, significantly shortens the scorch time and positive vulcanization time of the blended rubber, and significantly improves the mechanical properties, heat resistance and compression permanent deformation of the material.
[0073] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A heat-resistant and aging-resistant modified silicone rubber material, characterized in that: The raw materials include, by weight: 100 parts of vinyl silicone rubber, 3-12 parts of octahydrogen cage silsesquioxane, 6-18 parts of modified white carbon black, 3-12 parts of nano-sized tin oxide, 3-5 parts of ferric oxide, 1-10 parts of ethyl orthosilicate, 0.5-5 parts of dibutyltin dilaurate, and 1-3.8 parts of 2,6-di-tert-butyl-4-methylphenol; Under the action of an electric stirrer, the crosslinking agent octahydrogen cage silsesquioxane, the reinforcing filler modified white carbon black, the heat-resistant filler nano-sized tin oxide, the heat-resistant additive ferric oxide, the vulcanizing agent ethyl orthosilicate, and the catalyst dibutyl tin dilaurate are added to the vinyl silicone rubber in sequence, and after being fully stirred, the mixture is placed in a vacuum oven at room temperature to remove bubbles, the vacuum degree is controlled at -0.1 MPa, and the mixture is cured at room temperature to obtain a silicone rubber composite material.
2. The heat-resistant and aging-resistant modified silicone rubber material according to claim 1, characterized in that: The vinyl silicone rubber is polysiloxane containing vinyl end groups with a functionality of 2 or more and a polymerization degree of 1000 or more.
3. The heat-resistant and aging-resistant modified silicone rubber material according to claim 1, characterized in that: The octahydrogen cage silsesquioxane is prepared according to the following process: adding ferric chloride and concentrated hydrochloric acid to a container, then adding methanol, toluene and n-hexane to the container, stirring evenly, dissolving trichlorosilane in n-hexane, slowly dropping it into the container within 3 hours, and continuing to stir rapidly for 2 hours after the dropwise addition is completed. The reaction process is carried out at 30° C. and under the protection of N2 gas, the n-hexane layer is separated, anhydrous CaCL2 and anhydrous K2CO3 are added to the reaction solution, stirred and filtered, the filtered liquid is distilled under reduced pressure, concentrated until crystals are precipitated, the obtained product is collected, washed with n-hexane, and dried at 70° C. for 5 hours to obtain the product octahydrogen cage silsesquioxane, and the dried product octahydrogen cage silsesquioxane is purified to remove impurities and by-products therein; finally, pure octahydrogen cage silsesquioxane is obtained by a recrystallization method.
4. The heat-resistant and aging-resistant modified silicone rubber material according to claim 3, characterized in that: In the process of preparing octahydrogen cage-type silsesquioxane, the weight ratio of ferric chloride, concentrated hydrochloric acid, methanol, toluene, trichlorosilane and n-hexane is 15-50:5-30:10-40:10-55:5-15:120-280.
5. The heat-resistant and aging-resistant modified silicone rubber material according to claim 1, characterized in that The modified white carbon black is prepared according to the following process: white carbon black and an ionic liquid modifier are added into an electric stirrer in a certain proportion; The raw materials are fully stirred and mixed under the action of an electric stirrer so that the ionic liquid modifier is evenly coated on the surface of the silica. During the stirring process, an acetone solvent is added to promote the dissolution and dispersion of the ionic liquid. Then, the mixture is placed in a constant temperature water bath at 30° C. for reaction so that the ionic liquid modifier interacts with the functional groups on the surface of the silica. After the reaction is completed, the mixture is dried at a temperature of 150° C. for 3 hours to remove unreacted ionic liquid and solvent. The dried modified silica is sieved to remove impurities and uneven particles to obtain modified silica.
6. The heat-resistant and aging-resistant modified silicone rubber material according to claim 5, characterized in that: The ratio of the ionic liquid, white carbon black and acetone solvent is 10-50:500:1-5.
7. The heat-resistant and aging-resistant modified silicone rubber material according to claim 5, characterized in that: The ionic liquid is a dialkyl imidazole halide, the cation is a C4 or C6 alkyl substituent, and the anion is Cl - , the ionic liquid preparation process is as follows: Raw material preparation: alkyl imidazole and halogenated hydrocarbon are selected as raw materials, and sodium chloride is used as anion source; Synthesis reaction: Under the conditions of 85°C and 500 rpm stirring speed, alkyl imidazole and halogenated hydrocarbon are reacted for 3-5 hours to generate dialkyl imidazole halide intermediate; Then, the generated dialkyl imidazolium halide intermediate is subjected to anion exchange reaction with sodium chloride to generate the desired dialkyl imidazolium chloride ionic liquid. Post-treatment: washing, drying and purification are performed on the generated dialkyl imidazolium chloride ionic liquid to remove unreacted raw materials and impurities to obtain a pure ionic liquid.